2020
DOI: 10.1371/journal.pone.0243810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of primary payer status on the management and outcomes of ST-segment elevation myocardial infarction in the United States

Abstract: Background There are limited contemporary data on the influence of primary payer status on the management and outcomes of ST-segment elevation myocardial infarction (STEMI). Objective To assess the influence of insurance status on STEMI outcomes. Methods Adult (>18 years) STEMI admissions were identified using the National Inpatient Sample database (2000–2017). Expected primary payer was classified into Medicare, Medicaid, private, uninsured and others. Outcomes of interest included in-hospital mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Besides, we used validated codes that have been used extensively in prior studies using the NIS. 31 , 32 Second, the NIS does not capture pharmacotherapy, echocardiography, or angiographic data. Thus, granular information on the differences in antithrombotic regimes, ejection fraction, successful versus unsuccessful PCI, and reasons for not performing PCI is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we used validated codes that have been used extensively in prior studies using the NIS. 31 , 32 Second, the NIS does not capture pharmacotherapy, echocardiography, or angiographic data. Thus, granular information on the differences in antithrombotic regimes, ejection fraction, successful versus unsuccessful PCI, and reasons for not performing PCI is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Medicare patients are older and have higher comorbidities, and therefore may receive less frequent guideline-directed therapies because of risk of complications. 6,7 In contrast, though Medicaid patients are younger, hospitals are reimbursed lesser for Medicaid patients, raising concerns that they might systematically receive less aggressive therapy. 1,2 Cardiogenic shock (CS) constitutes the sickest spectrum of AMI, and continues to be associated with nearly 30% to 40% mortality and morbidity in the contemporary era.…”
mentioning
confidence: 99%
“…Typically, privately insured individuals receive the most aggressive care when presenting with an AMI and, therefore, it is important to contrast the outcomes of uninsured group against this insurance group. 1,2,6,7 Considering this background, using a nationally representative population, we sought to assess the management and outcomes of uninsured individuals compared with privately insured individuals presenting with AMI-CS. In addition, we evaluated the temporal trends in admissions, use of cardiac and noncardiac procedures, and clinical outcomes of these populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, it has been previously shown that socioeconomic characteristics such as 'primary expected payer' status and 'median household income' are associated with worse outcomes in patients with principal discharge diagnosis of AMI through disparities in the receipt of evidence-based therapies and guideline recommended care. 21,22 However, in order to diminish the influence of these variables, we have conducted a multivariable logistic regression analysis and adjusted for them.…”
Section: Discussionmentioning
confidence: 99%